(untitled) (Journal of Biomedical Investigation, 2025)
Chronic wounds such as diabetic foot ulcers, pressure ulcers, and venous leg ulcers pose a significant global health burden due to prolonged healing, recurrent infections, and high treatment costs. Traditional wound care often fails to adequately manage these complexities with chronic wounds, particularly when complicated by biofilm forming, antibiotic-resistant pathogens. This narrative review evaluates the therapeutic potential of two non-invasive biophysical modalities: Light Amplification by Stimulated Emission of Radiation (LASER) and Transcutaneous Electrical Nerve Stimulation (TENS) for chronically infected wounds. LASER therapy promotes healing through photo-biomodulation by enhancing mitochondrial activity, angiogenesis, collagen synthesis, photodynamic bacterial destruction. and TENS facilitates healing via pain modulation, improved microcirculation, reduced inflammation, and fibroblast stimulation. Clinical and preclinical evidence highlights the efficacy of both modalities in accelerating wound closure, promoting tissue regeneration, and reducing infection. Furthermore, combining LASER and TENS may offer synergistic benefits by targeting multiple aspects of wound pathophysiology. Although current evidence is promising, further randomized controlled trials are necessary to establish standardized protocols and evaluate long-term outcomes. Integrating LASER and TENS into multidisciplinary wound care could significantly enhance healing in patients with chronic wound infections.